Psycholinguistic and Psychometric Measurements of the Turkish Pediatric Epilepsy Medication Selfmanagement Questionnaire - Şerife Tutar; Ayşegül İşler Dalgıç (Galenos Yayinevi, 2021)
Aim:The aim of this study was to examine the psychometric and psycholinguistic characteristics of "The Pediatric Epilepsy Medication Self-management Questionnaire" which was adapted into Turkish.Materials and Methods:The sample of this methodological study consisted of 540 parents whose children (between the ages of 2-17 years) were followed up at Akdeniz University Hospital Pediatric Neurology Polyclinic between April 2015 and June 2016 with a diagnosis of epilepsy. The data of the study was grouped into 4 sub-dimensions. A face-to-face interview method was conducted by the researcher using "The Child and Parent Introduction Form" and "The Pediatric Epilepsy Medication Self-management Questionnaire". Written informed consent was obtained from Akdeniz University Clinical Research Ethics Committee and the parents.Results:Scoring received from 10 specialists was assessed to evaluate the scales scope validation and it was determined that there was agreement between the specialists (content validity index=0.89). The Kaiser-Meyer-Olkin value of 0.656 and Barlett's test value of (df=210, p=0.000) indicated that the data were sufficient in amount and suitable for factor analysis. As a result of exploratory factor analysis, 6 items for which factor loads were below 0.40 were removed from the scale. The factor structure of the newly formed 4 sub-dimension scale was tested by confirmatory factor analysis and the structure was confirmed (χ2/df=2.372, root mean square error of approximation=0.079, comparative fit index=0.901, goodness of fit index=0.927 and adjusted goodness of fit index=0.851). The Cronbach Alpha coefficient was found to be 0.71 for the total score of the scale. The sub-dimension correlations of the scale were determined to vary between 0.829-0.690. The testing correlations for test-retest were found to be significant (p<0.001) and high (0.91).Conclusion:The Turkish adapted version of "The Pediatric Epilepsy Medication Self-management Questionnaire" was determined to band reliably for Turkish society.